The reality of employing Blockchain technology in the educational process in Saudi universities from the point of view of faculty members - Al-Sawat, Shorouk Abdullah Tael (Journal of Educational and Psychological Sciences, 2023)
The study aimed to know the reality of employing block technology in the educational process in Saudi universities by knowing the degree of readiness of Saudi universities to employ the Internet of Things in the educational process, and the importance and obstacles to its employment from the point of view of faculty members in Saudi universities. To achieve the objectives of the study, the researcher used the analytical descriptive approach, by applying a questionnaire that was applied to a sample of (382) faculty members in five Saudi universities representing the regions of the Kingdom of Saudi Arabia. Chain in the educational process was average, and the importance of employing blockchain in the educational process in Saudi universities came from the point of view of faculty members with a high degree. Where the general average was equal to (4.07) and the degree of agreement was (high). The study sample also agreed that there are obstacles that prevent the use of blockchain in the educational process in Saudi universities. Where the general mean was equal to (4.03) and the degree of agreement (high), and in light of the results of the study, The study recommended a number of recommendations, the most important of which are: working to reduce the obstacles that prevent the use of blockchain in the educational process.